Tendances du secteur de l'elevage en Afrique au sud du Sahara - Anteneh, A. (1984)
Describes the situation in sub-Saharan Africa's livestock industries over the last two decades, reviewing the most important trends in Africa's livestock industries, with particular reference to meat & milk output from ruminant livestock, & the external trade in these commodities; & considering these trends on the basis of a regional comparison of the situation in four subregions of sub-Saharan Africa. Examines the resource base & the changes that have taken place in it over the last 20 years, assessing factors affecting output & discussing the implications for livestock policy in sub-Saharan Africa.